FIRES IN TECHNOSPHERE AND PRINCIPLES OF PROTECTION AGAINST THEM - Ashurova , Loyla (Innovative Development in Educational Activities, 2023)
The article describes fires in the technosphere and their causes, preventive and technical measures against fires, factors affecting the human body, and fire suppression methods. Fire-resistant materials are analyzed, ways to increase the level of fire resistance of buildings and structures are shown. The main problems of fire detection in high-rise residential buildings, the procedure for using automatic fire detection devices and fire extinguishing equipment and their use are presented.